Electric field effect on polarization and depolarization behavior of the 〈0 0 1〉-oriented relaxor-based 0.7Pb(Mg1/3Nb2/3)O3–0.3PbTiO3 single crystal - Chew, Khian Hooi; Luo, H.; Zhao, X.Y.; Wang, J.; Peng, Z.; Chan, H.L.W.; Choy, C.L. (Elsevier, 2003)
Polarization and depolarization behavior of the <0 0 1>-oriented relaxor-based 0.7Pb(Mg1/3Nb2/3)O-3-0.3PbTiO(3) single crystal were investigated through biased dielectric measurement, thermally stimulated discharging current and polarization-electric field (P-E) hysteresis loop measurements. The reversal of discharging current and the increase of remnant polarization with increasing temperature were observed in the depolarization process of the <0 0 1>-poled crystal upon heating. The biased dielectric response shows the existence of the transition between two macrodomain ferroelectric phases. It is proposed that an electric field applied along the <0 0 1> direction could induce a ferroelectric tetragonal phase, which mediates between the lower temperature ferroelectric rhombohedral phase and higher temperature paraelectric cubic phase. (C) 2003 Elsevier B.V. All rights reserved.